Zebrafish Housing : The Recirculating and Cost-effective Open Design Aquaria System - Siti Zaleha, Raduan; Qamar Uddin, Ahmed; Muhamad Rusdi, Ahmad Rusmili; Awis Sukarne, Mohmad Sabere; Muhammad Salahuddin, Haris; Mohd. Farooq, Shaikh; Wan Azizi, Wan Sulaiman; Nor Asyikin, Zukifli; Muhammad Hamdi, Mahmood (UPM Press, 2024)
The zebrafish’s ease of care and high reproductive rate have made them a popular animal model. It is routinely kept and maintained in commercial aquariums. However, the expense of a particular system was prohibitive for researchers with limited budgets or who worked in universities without zebrafish-rearing facilities. Thus, a simple custom-made aquaria system was developed. The recirculating opendesign aquaria system was cost-effective and may frequently be improved. This study has developed a distinctive aquaria system that can tackle the issues related to expanding research based on zebrafish.